2007
DOI: 10.1300/j015v30n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services Seeking in Sexual Assault Victims

Abstract: Sexual assault victims experience significant mental health sequelae from being victimized. Despite these psychological symptoms, survivors seek traditional mental health services at low rates. Little research has addressed the potential barriers that may lead to lower rates of mental health service seeking or whether these services in fact help survivors to recover from the psychological impact of sexual assault. This paper reviews literature on sexual assault victimization and mental health service seeking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 98 publications
3
79
0
Order By: Relevance
“…Considerably more victims report telling informal sources of support about their experiences. The same pattern has been reported among both men and women in international research (Ullman, 2007;Postmus et al, 2009;Ansara and Hindin, 2010;Fanslow and Robinson, 2010;McCart et al, 2010). In accordance with this a need to talk to professionals about their victimization was expressed by some of the men in study IV, some also said that the support they received from family and friends was enough.…”
Section: The Risk Of Medicalizationsupporting
confidence: 79%
See 2 more Smart Citations
“…Considerably more victims report telling informal sources of support about their experiences. The same pattern has been reported among both men and women in international research (Ullman, 2007;Postmus et al, 2009;Ansara and Hindin, 2010;Fanslow and Robinson, 2010;McCart et al, 2010). In accordance with this a need to talk to professionals about their victimization was expressed by some of the men in study IV, some also said that the support they received from family and friends was enough.…”
Section: The Risk Of Medicalizationsupporting
confidence: 79%
“…For example, women who have been victimized both in childhood and adulthood are found to be at a higher risk of living with low social support than are women victimized only as children, or only as adults (Schumm et al, 2006). Positive social support after trauma has been found to be associated with less somatic symptoms as well as better perceived health among female victims of sexual violence (Ullman, 2007). Likewise, among female victims of intimate partner violence, perceived high levels of social support have been associated with reporting less symptoms of depression (Coker, Smith, Thompson et al, 2002b;Mburia-Mwalili, Clements-Nolle, Lee et al, 2010), and social support has been found to be a protective factor against self-reported posttraumatic stress symptoms among adult victims of childhood abuse (Stevens et al, 2013).…”
Section: Interpersonal Violence and Symptoms Of Psychological Ill-healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research, we hypothesized that experiencing more than one assault, history of psychopathology, and history of substance abuse would be positively associated with ever seeking help (5,8,19). In regard to specific rape types, it was thought that forcible rape would be associated with increased likelihood of ever seeking help as compared to other types of rape (17).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The experience of sexual violence can have profound psychological effects on an individual. Despite this, few survivors seek professional help (Parcesepe, Martin, Pollock, & GarcĂ­a-Moreno, 2015; Ullman, 2007). This project will identify barriers and facilitators to seeking and accessing help in the wake of a sexual assault.…”
Section: Introductionmentioning
confidence: 99%